Efficacy of a recombinant single-chain fragment variable region, VasSF, as a new drug for vasculitis [Corrigendum] - Kameoka Y; Kishi F; Koura M; Yamakawa Y; Nagasawa R; Ito F; Matsuda J; Suzuki O; Nakayama T; Suzuki K (Dove Medical Press, 2019)
Kameoka Y, Kishi F, Koura M, et al. Drug Des Devel Ther. 2019;13:555–568.  The authors have advised that there was an error in the text.  Page 561, beginning at the left-hand bottom of the page, “The number of peripheral blood lymphocytes and granulocytes did not change in the aVAP2-administered mice: WBCs: 4.42 (1.36–7.57)×109 cells/L vs 3.14 (1.48–15.7)×109 cells/L (Figure S3A). The number of granulocytes decreased: 0.15 (0.05–1.04)×109 cells/L vs 0.22 (0.04 0.69)×109 cells/L (Figure S3B).” should instead read “The number of peripheral blood lymphocytes and granulocytes did not change in the aVAP2-administered mice: WBCs: 2.11 (1.36–2.44)×109 cells/L vs 3.14 (1.48–15.7)×109 cells/L (Figure S3A). The number of granulocytes decreased: 0.055 (0.03–0.08)×109 cells/L vs 0.22 (0.04–0.69)×109 cells/L (Figure S3B).”  Read the original article